2019
DOI: 10.1007/s10096-018-03452-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of erythrocytes on bacterial growth and antimicrobial activity of selected antibiotics

Abstract: It has been shown that protein binding, temperature, and pH influence in vitro pharmacodynamic (PD) models. The fact that corpuscular blood compounds might also have an important impact is something which has, until now, often been neglected. We investigated if the addition of human erythrocytes to standard growth media (Mueller Hinton Broth, MHBII) has an influence on bacterial growth behavior and on antibiotic efficacy. We did this by using bacterial growth assays and time kill curves (TKC) of selected strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…Analysis was done for MHB Throm and MHB Ref , for ciprofloxacin and meropenem at a final concentration of 0.1 μg/mL and at 1 μg/mL for tigecycline. The procedure was performed in analogy to erythrocyte experiments recently published [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis was done for MHB Throm and MHB Ref , for ciprofloxacin and meropenem at a final concentration of 0.1 μg/mL and at 1 μg/mL for tigecycline. The procedure was performed in analogy to erythrocyte experiments recently published [4].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the impact of potential factors on the interplay between pathogens and antimicrobial agents should be individually assessed. Host factors such as pH, protein binding, and cations, as well as corpuscular blood components such as erythrocytes have been shown to impact activity of antibiotics and/or growth of the pathogen [1][2][3][4]. Nevertheless, the impact of thrombocytes, which may be equally relevant, has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Even though 100% serum might be a good option to resemble in vivo conditions, studies have already shown that pure serum is less optimal in terms of bacterial growth compared to standard growth media, such as MHB [ 19 , 37 ]. Thus, many studies test the impact of the addition of serum to growth media in various concentrations, ranging from 20% to 100% [ 16 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Published In Vitro Studiesmentioning
confidence: 99%
“…Another important factor playing a role in adsorption of antibiotics on filter membrane is the presence of blood proteins and cellular blood components [ 11 , 12 ]. The presence of proteins and erythrocytes decreases the free fraction of a drug available for binding to filter membrane, but on the other hand proteins bound to antibiotics may also be adsorbed on the filter [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor playing a role in adsorption of antibiotics on filter membrane is the presence of blood proteins and cellular blood components [ 11 , 12 ]. The presence of proteins and erythrocytes decreases the free fraction of a drug available for binding to filter membrane, but on the other hand proteins bound to antibiotics may also be adsorbed on the filter [ 11 ]. There may be two stages of serum protein adsorption on the filter surface: the first one involving adsorption of proteins with high molecular weight on the filter surface (for example albumins) and the second stage consisting in adsorption of proteins inside the membrane (proteins of low or medium molecular weight).…”
Section: Introductionmentioning
confidence: 99%